The analysis of consumer behavior and tourism resilience post-pandemic covid-19 in Belitung Regency - Mayasari, Dessy; Zubaidah, Ida (Jurnal Pariwisata Pesona, 2025)
The COVID-19 pandemic has had a significant impact on the tourism sector, as reflected in the decline in tourist visits and the decrease in community income, particularly among micro, small, and medium enterprises (MSMEs). The Belitung Regency Government has implemented various policies to rebuild tourism resilience in the post-pandemic era, including the enforcement of health protocols. However, these measures have not fully restored the sector to its pre-pandemic stability. This study aims to analyze the effectiveness of government policies in restoring the tourism sector and to assess the economic resilience of the local community using a mixed-method approach. In-depth interviews were conducted with policy stakeholders through purposive sampling, while quantitative data were obtained by distributing questionnaires to tourists in order to identify consumer behavior characteristics. The findings reveal that destination attractiveness and the strength of local brands are key factors influencing tourists’ decisions to visit. The analysis of consumer behavior indicates that most behavioral indicators have been fulfilled, although they remain at a moderate level. Several challenges hinder further improvement, including suboptimal operational standards for disease prevention, insufficient environmental management, and limited supporting infrastructure such as public transportation and non-Jakarta flight access.